Development of a methods repository for food choice behaviors and drivers at the household and individual levels - Boncyk, Morgan; Isanovic, Sejla; Samin, Sharraf; Rampalli, Krystal K.; Frongillo, Edward A.; Avula, Rasmi; Kim, Sunny S.; Scott, Samuel P.; Blake, Christine E. (International Food Policy Research Institute, 2023)
This brief identifies important constructs for assessing drivers of food choice behaviors and describes progress on the development of a repository of instruments and measures for assessing these constructs. OBJECTIVES 1. List constructs that can be assessed to understand drivers of household and individual food choice behaviors. 2. Identify instruments and measures to assess each food choice construct and organize these into a searchable repository. 3. Illustrate the use of the Food Choice Repository.